2010
DOI: 10.1007/s12928-010-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and clinical outcomes of 100 consecutive severe calcified lesions requiring rotational atherectomy prior to sirolimus-eluting stent implantation in hemodialysis and non-hemodialysis patients

Abstract: Both severe calcified lesions and hemodialysis (HD) are predictors for high rates of restenosis, even in the drug-eluting stent era. We sought to investigate the angiographic and clinical outcome in a population of HD versus non-hemodialysis (non-HD) patients with severe calcified lesions requiring rotational atherectomy. One hundred consecutive lesions (28 lesions in the HD group, 72 in the non-HD group) from 82 patients (19 patients in the HD group, 63 in the non-HD group) requiring rotational atherectomy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…13 Kyono et al also reported that both angiographic and clinical outcomes were still suboptimal for highly complex, severely calcified lesions requiring RA in patients with hemodialysis, even when using DES. 25 The present study provides one of the largest sets of observational data with the longest follow-up period, and confirms a 21.5% rate of cardiac death, similar to other registry data from smaller samples with shorter follow-up. In contrast, statin use was the only significant predictor associated with more positive outcomes on multivariate analysis.…”
Section: Long-term Clinical Outcomessupporting
confidence: 89%
“…13 Kyono et al also reported that both angiographic and clinical outcomes were still suboptimal for highly complex, severely calcified lesions requiring RA in patients with hemodialysis, even when using DES. 25 The present study provides one of the largest sets of observational data with the longest follow-up period, and confirms a 21.5% rate of cardiac death, similar to other registry data from smaller samples with shorter follow-up. In contrast, statin use was the only significant predictor associated with more positive outcomes on multivariate analysis.…”
Section: Long-term Clinical Outcomessupporting
confidence: 89%
“…In addition, several studies have identified dialysis as the strongest predictor of adverse outcomes after PCI . The increased risk of adverse outcomes among patients with CKD, particularly those on HD, might be associated with the severity of calcified lesions, enhanced platelet activation, and differences in the physiological measurement of fractional flow reserve . Coronary in‐stent restenosis among patients with CKD might also result from neointimal hyperplasia, a very complex process that is influenced by several pathophysiological mechanisms, including vascular inflammation, an increase of calcification promoters and the activation of the renin‐angiotensin system, resulting in an enhanced production of reactive oxygen species …”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 ) Rotablator can theoretically facilitate stent delivery and stent expansion as well as avoidance of polymer damage. Several studies evaluated clinical outcomes after rotational atherectomy and SES implantation between hemodialysis and non-hemodialysis patients with severely calcified lesions; they found that clinical outcomes were significantly worse in hemodialysis patients than in non-hemodialysis patients 38 40 ) ( Fig. 2 ).…”
Section: Percutaneous Coronary Interventionmentioning
confidence: 99%